PCV20 in pediatric pneumococcal prevention: expanded coverage, remaining challenges - Principi, Nicola; Argentiero, Alberto; Campana, Beatrice; Esposito, Susanna (Frontiers in Immunology, 2026)
Pneumococcal conjugate vaccines (PCVs) have substantially reduced the global burden of Streptococcus pneumoniae infections in children, yet serotype replacement and variability in immunogenicity continue to challenge long-term effectiveness. The recent introduction of the 20-valent vaccine (PCV20), which adds seven serotypes to those covered by PCV13, represents an important advance as these additional serotypes—such as 8, 10A, 11A, 12F, 15B, 22F, and 33F—are now recognized as significant contributors to invasive and noninvasive pneumococcal disease. To evaluate the potential and limitations of PCV20, we conducted a systematic literature search across PubMed, Scopus, and Web of Science through July 2025, supplemented by manual reference screening, including randomized trials, observational studies, systematic reviews, meta-analyses, and official reports from WHO, CDC, EMA, and FDA. Current evidence indicates that PCV20 elicits broadly noninferior immune responses compared to PCV13, though weaker responses have been observed for specific serotypes, notably 3, 6B, 9V, 19A, and 23F. Mathematical models suggest PCV20 could prevent thousands of additional pneumococcal cases annually compared with PCV13 or PCV15, but other analyzes predict increased breakthrough infections, particularly under reduced-dose regimens. The vaccine’s effectiveness may also be limited by the potential for new serotype replacement, and concerns persist regarding its performance in 2 + 1 or 1 + 1 schedules, with regulatory agencies currently approving only the 3 + 1 regimen. These findings highlight PCV20 as a promising step in pneumococcal prevention but not a definitive solution. Continued surveillance, real-world effectiveness studies, and accelerated development of next-generation higher-valency vaccines will be essential to sustain and expand protection against pneumococcal disease in children.